The secreted polyketide boydone A is responsible for the anti-Staphylococcus aureus activity of Scedosporium boydii. Issue 22 (24th October 2017) - Staerck, Cindy; Landreau, Anne; Herbette, Gaëtan; Roullier, Catherine; Bertrand, Samuel; Siegler, Benjamin; Larcher, Gérald; Bouchara, Jean-Philippe; Fleury, Maxime J J
Abstract: Usually living as a soil saprophyte, the filamentous fungus Scedosporium boydii may also cause various infections in human. Particularly, it is one of the major causative agents of fungal colonization of the airways in patients with cystic fibrosis (CF). To compete with other microorganisms in the environment, fungi have evolved sophisticated strategies, including the production of secondary metabolites with antimicrobial activity that may also help them to establish successfully within the respiratory tract of receptive hosts. Here, the culture filtrate from a human pathogenic strain of S. boydii was investigated searching for an antibacterial activity, mainly against the major CF bacterial pathogens. A high antibacterial activity against Staphylococcus aureus, including methicillin-resistant strains of this species, was observed. Bio-guided fractionation and analysis of the active fractions by nuclear magnetic resonance or by high-performance liquid chromatography and high-resolution electrospray ionization-mass spectrometry allowed us to identify boydone A as responsible for this antibacterial activity. Together, these results suggest that this six-membered cyclic polyketide could be one of the virulence factors of the fungus. Genes involved in the synthesis of this secreted metabolite are currently being identified in order to confirm the role of this polyketide in pathogenesis. Abstract : This article deals about purification of boydone A from culture filtrate of Scedosporium boydii, a polyketide with anti- Staphylococcus aureus activity.